Current and future targets for faecal microbiota transplantation. (March 2019) - Mcilroy, James Roger; Segal, Jonathan P.; Mullish, Benjamin H.; Nabil Quraishi, Mohammed; Gasbarrini, Antonio; Cammarota, Giovanni; Ianiro, Gianluca
Abstract: The human gastrointestinal tract is home to the most diverse microbial ecosystem in the human body and is made up of bacteria, viruses and eukarya. Collectively known as the gut microbiota, our knowledge of these microbial communities has historically been restricted by the relative limitations of culturing techniques. However, the recent development and utilisation of next-generation sequencing techniques has enhanced our understanding of its structure, diversity and function. There is emerging evidence that the gut microbiota plays a pivotal role in both health and disease. Perturbations to the structure and function of the gut microbiota are known to be associated with certain disease states. Therefore, manipulating the gut microbiota in an attempt to restore structure and function represents a promising therapeutic strategy. Recently, there has been a surge in clinical and scientific interest in manipulating the gut microbiota using a method called faecal microbiota transplantation. This increase in interest has gathered after it was shown in randomised controlled trials to be highly effective in treating recurrent Clostridium difficile infection. Despite success in treating recurrent Clostridium difficile, there remain many unknowns about how best to optimise its preparation, regulation, mode of delivery and safety. This review aims to summarise the literature surrounding the current knowledge regarding faecal microbiota transplantation and explore potential future research avenues that aim to enhance the safety, efficacy and utilisation of faecal microbiota transplantation.